Effect of Irrigation to Winter Wheat on the Radiation Use Efficiency and Yield of Summer Maize in a Double Cropping System - Li Quanqi; Chen Yuhai; Zhou Xunbo; Yu Songlie; Guo Changcheng (The Scientific World Journal)
In north China, double cropping of winter wheat and summer maize is a widely adopted agricultural practice, and irrigation is required to obtain a high yield from winter wheat, which results in rapid aquifer depletion. In this experiment conducted in 2001-2002, 2002-2003, and 2004-2005, we studied the effects of irrigation regimes during specific winter wheat growing stage with winter wheat and summer maize double cropping systems; we measured soil moisture before sowing (SMBS), the photosynthetic active radiation (PAR) capture ratio, grain yield, and the radiation use efficiency (RUE) of summer maize. During the winter wheat growing season, irrigation was applied at the jointing, heading, or milking stage, respectively. The results showed that increased amounts of irrigation and irrigation later in the winter wheat growing season improved SMBS for summer maize. The PAR capture ratio significantly (LSD, P<0.05) increased with increased SMBS, primarily in the 3 spikes leaves. With improved SMBS, both the grain yield and RUE increased in all the treatments. These results indicate that winter wheat should be irrigated in later stages to achieve reasonable grain yield for both crops.